2018
DOI: 10.1177/0961203317749046
|View full text |Cite
|
Sign up to set email alerts
|

Trends in use of hydroxychloroquine during pregnancy in systemic lupus erythematosus patients from 2001 to 2015

Abstract: Background Evidence suggests that continuing hydroxychloroquine (HCQ) during pregnancy in women with systemic lupus erythematosus (SLE) improves outcomes. We sought to describe time trends in the continuation, initiation, and duration of HCQ in a large population-based cohort of pregnant SLE women. Methods A cohort of pregnant women with SLE enrolled continuously in public (Medicaid, 2001-2010) or private (Optum Clinformatics, 2003-2015) health insurance between three months prior to conception and one month a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
2
22
1
Order By: Relevance
“…Due to its beneficial effects and good safety profile, the use of antimalarial drugs during gestation in women with SLE has increased in the present century. 51,52 Several studies have shown the beneficial effects of hydroxychloroquine on maternal-fetal outcomes, including decrease of lupus flares, prematurity rates, intrauterine growth restriction and even improvement in the rate of fetal loss. [53][54][55][56][57][58] However, information on the role of antimalarial drugs in preeclampsia is more limited.…”
Section: F I G U R E 1 Kaplan-mentioning
confidence: 99%
“…Due to its beneficial effects and good safety profile, the use of antimalarial drugs during gestation in women with SLE has increased in the present century. 51,52 Several studies have shown the beneficial effects of hydroxychloroquine on maternal-fetal outcomes, including decrease of lupus flares, prematurity rates, intrauterine growth restriction and even improvement in the rate of fetal loss. [53][54][55][56][57][58] However, information on the role of antimalarial drugs in preeclampsia is more limited.…”
Section: F I G U R E 1 Kaplan-mentioning
confidence: 99%
“…18 HCQ is recognized as being safe for use during pregnancy and breastfeeding, and this property is especially important for women in malaria-endemic regions. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] A study of 133 pregnant women with connective tissue disease found that HCQ was safe when compared to a control group. 24 Historically, HCQ has been used by rheumatologists and obstetricians to treat women with autoimmune disease to minimize flares and improve pregnancy outcome.…”
Section: History Of Hcqmentioning
confidence: 99%
“…Reproductive immunologists have used HCQ to calm overactive immune systems with good outcomes in women who suffer from immunological pregnancy loss and/or failure. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Although HCQ has been criticized for prolonging the QT interval, numerous other medications are known to have a greater effect on this EKG parameter without significant clinical concerns, and the safety of HCQ in COVID-19 treatment trials involving nearly 3000 outpatients has recently been confirmed. [34][35][36]…”
Section: History Of Hcqmentioning
confidence: 99%